2007
DOI: 10.1590/s0006-87052007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e produção do capim-pé-de-galinha e da soja cultivada em sucessão em sistema antecipado de adubação

Abstract: RESUMOArgumenta-se sobre a viabilidade de manejo químico do solo estar relacionado à adubação de todo o sistema de cultivo (adubação antecipada) visando promover o incremento de material orgânico no agroecossistema, devido as suas inúmeras vantagens no aspecto da conservação do solo, preservação dos recursos naturais renováveis e na reciclagem dos nutrientes; ou mantém-se o tradicional sistema de adubação de base, isto é, aplicação de fertilizantes simultaneamente à semeadura da cultura. O objetivo deste traba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
1
10
0
6
Order By: Relevance
“…Consequently, the P export through maize grain harvest is higher. According to Guimarães et al (2006), for 7,729 kg ha -1 grain yield, maize exports about 32 kg ha -1 P, which is higher than the 16 kg ha -1 P exported by 3,494 kg ha -1 of soybean grain (Francisco et al, 2007), and 6 kg ha -1 P exported with bean, with a grain yield of 1,758 kg ha -1 (Andrade et al, 2004). Additionally, the results may also have been influenced by slower decomposition of grass residues with higher C/N ratio, reducing decomposition rate and P release, compared to leguminous species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the P export through maize grain harvest is higher. According to Guimarães et al (2006), for 7,729 kg ha -1 grain yield, maize exports about 32 kg ha -1 P, which is higher than the 16 kg ha -1 P exported by 3,494 kg ha -1 of soybean grain (Francisco et al, 2007), and 6 kg ha -1 P exported with bean, with a grain yield of 1,758 kg ha -1 (Andrade et al, 2004). Additionally, the results may also have been influenced by slower decomposition of grass residues with higher C/N ratio, reducing decomposition rate and P release, compared to leguminous species.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, the explanation could be the use of bean as a summer crop in the previous growing season (2005/2006). According to Andrade et al (2004), this crop exports 20 kg ha -1 K through grain harvest, which is low compared to maize and soybean, with 45 kg ha -1 (Guimarães et al, 2006) and 56 kg ha -1 (Francisco et al, 2007), respectively. Due to the low K export, a great amount is traken up by plants and remains in the leaves, stems and roots.…”
Section: Resultsmentioning
confidence: 99%
“…A produção de biomassa seca do capim-pé-degalinha atingiu 5.210 kg ha -1 de biomassa seca, em plantio de verão no Estado de São Paulo (Muraishi et al, 2005), enquanto Franscisco et al (2007), em Piracicaba (SP), semeando em setembro e manejando no pleno florescimento com a adubação antecipada, obtiveram a produção de 6.375 kg ha -1 de biomassa seca. Em condições de safrinha, no sudoeste de Goiás, o rendimento desta cultura foi de 9.480 kg ha -1 (Assis et al, 2005) e no Piauí foi de 2.890 kg ha -1 de biomassa seca (Azevedo & Nascimento, 2002).…”
Section: Introductionunclassified
“…Ruzigrass and P sources did not interact as to soybean yields and leaf-P contents. Francisco et al (2007) reported that P fertilization of increased finger millet (Eleusine coracana) biomass production, but had no effect on subsequent soybean yield.…”
Section: Resultsmentioning
confidence: 99%